Model Pembinaan Karakter Religius untuk Meningkatkan Keimanan dan Ketaqwaan Mahasiswa melalui Organisasi Mahasiswa FSI KU - Ridho Fadhilah; Aceng Kosasih (Neolectura, 2020)
Various problems of education in nowadays is often the case of moral damage or akhlaqul karimah children. The more distant children of the nation with religious values one of them seemed to the student lifestyle at this time. The purpose of this research is to explain the religious character coaching programs by the FSI Student organization and explain the results of the formation of religious characters. This research uses qualitative descriptive methods, its location at the State University of Jakarta, data sources of primary and secondary, the techniques of collecting data on observations, interviews, documentation, using data reduction, presentation Withdrawal conclusions. The results of this study authors found that the pattern of building religious character through the student organization FSI KU, among others, increasing the devotion of student worship, increased attitude of student tolerance, increased honest attitudes of students, and attitudes Istiqomah students, this is all seen through the monitoring of organizational managers and the polls that are disseminated